A rush to injustice : how power, prejudice, racism, and political correctness overshadowded truth and justice in the Duke lacrosse rape case /: how power, prejudice, racism, and political correctness overshadowded truth and justice in the Duke lacrosse rape case. (c2007) - Unknown
No abstract available